The Hidden Danger: Unintended Overdose With Prescription Medication Due to Non-Medical Use - Guggisberg, Marika (International Journal of Arts and Sciences, 2013)
The non-medical use of pharmaceuticals, which is defined as the intentional intake of medication that is not medically necessary, has become recognised as a public health problem. Many women engaged in non-medical prescription use suffer concurrent mental health problems, often associated with the current and/or past exposure to violence in the home. In these cases, complex clinical presentations are to be entangled, with reports that the substances are used as a coping mechanism, particularly, when sexual violence is part of the victimisation history. This article provides insight into the complex interplay between victimisation experiences, mental health problems and substance use as well as the increased recognition of the danger of accidental overdoses. It demonstrates the importance of flexible multidisciplinary support from specialist services for clients who present with multiple comorbidities and vulnerabilities. As such, the article advocates for multidisciplinary management, which allows assisting women with complex presentations utilising collaborative care provided by an interdisciplinary team.